The Contribution of PT Petrokimia Gresik to the Achievement of the SDGs: A Perspective of Sustainability and Accountability – A Study of the 2023 Annual Report - Citra , Helena Rahmawati (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to analyze the contribution of PT Petrokimia Gresik in supporting the achievement of the Sustainable Development Goals (SDGs) through sustainability strategies and transparent performance reporting. Using a descriptive qualitative approach and content analysis method, this research examines the company’s 2023 sustainability report, which is prepared in accordance with the Global Reporting Initiative (GRI) guidelines. The main focus of the study lies in the extent to which the company discloses SDG indicators and how the integration of Environmental, Social, and Governance (ESG) principles is reflected in its operational activities and social responsibilities. The programs not only contribute to improving community welfare but also strengthen food security and maintain ecological balance. Moreover, the company actively integrates the principles of transparency and accountability in its reporting by preparing a report separate from the annual report and publishing it openly to the public. With the attainment of the “Platinum” award in the 2023 Asia Sustainability Reporting Rating (ASRRAT), PT Petrokimia Gresik is considered to have successfully demonstrated a genuine commitment to accountable sustainability reporting. This study emphasizes the importance of high-quality reporting practices, which can serve as a reference for other companies in preparing sustainability reports that align with international standards and support sustainable development.